Cykl życia wirtualnego outsourcingu informatycznego - Dziembek, Damian (The Life Cycle of Virtual Outsourcing on Information Systems, 2007)
The aim of this article is presentation the life cycle of virtual outsourcing on information systems. The virtual outsourcing on information systems can be a new form of outsourcing IT realization. This article presents main phases of virtual outsourcing on information systems: planning, organizing, realization (operation), development or termination. The virtual outsourcing on information systems has chance to become a very interesting conception for new enterprises like virtual enterprises or virtual organizations.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (10); 2007; nr 1150, s. 226-238